Development of hybrid electrodeposition/slurry diffusion aluminide coatings on Ni-based superalloy with enhanced hot corrosion resistance - Zakeri, Ali; Masoumi Balashadehi, Mohammad Reza; Sabour Rouh Aghdam, Alireza (Journal of Composites and Compounds, 2021)
Ni/Co-modified aluminide coatings were prepared on the Hastelloy-X superalloy by a combined process of electrodeposition and slurry aluminizing. In this regard, pure layers of Ni and Ni-50wt.%Co were initially applied via electrodeposition process and successive aluminization was carried out by a slurry technique. The scanning electron microscopy (SEM) and X-ray diffraction (XRD) techniques were used for the microstructural and chemical composition characterization of the specimens. The results of these analyses revealed that a compact and dense aluminide coating was formed with a two-layered structure containing the outer Al-rich B phase and inner interdiffusion zone. Moreover, the presence of pre-electrodeposited layers inhibited the outward diffusion flux of elements from the substrate and effectively suppressed the formation of Kirkendall pores. The hot corrosion studies of the obtained coatings indicated that the addition of a pre-electrodeposited layer could enhance the high-temperature corrosion performance of the coatings when exposed to sulfate salt.